PENGARUH RASIO L/D ANTARA LAPISAN MORTAR GEOPOLIMER BERBAHAN DASAR FLY ASH TERHADAP KUAT TEKAN BETON DENGAN SEAWATER CURING - Nastiti, Syahidah Fani (Jurnal Qua Teknika, 2023)
ABSTRAK The performance and durability of concrete in construction is essential to maintain the sustainability and protection of the material. Particularly in construction in marine environments, the attack of aggressive chemical compounds can affect concrete and accelerate deterioration. This research aims to improve the performance and durability of concrete in construction in marine environments by using additional protection methods such as Surface Applied Protection. One of the materials used is geopolymer mortar that uses fly ash as a base material. This study shows that geopolymer mortar contributes positively to the compressive strength and durability of concrete. The thickness of the geopolymer mortar layer affected the mechanical properties of the concrete, and 4 cm thick gave the highest compressive strength results. The addition of geopolymer mortar needs to be adjusted to the compressive strength of the concrete and pay attention to the layer thickness for optimal results. Kata kunci: repair material, marine environment, L/D ratio, geopolymer mortar, compressive strength